Human interferon B1 ser17: Coding DNA synthesis, expression, purification and characterization of bioactive recombinant protein - Villela Dr, Anne; Renard, Gaby; Palma, Mario Sergio [UNESP]; Chies, Jocelei Maria; Dalmora, Sérgio Luiz; Basso, Luiz Augusto; Santos, Diógenes Santiago (OMICS International, 2010)
A protocol to produce large amounts of bioactive homogeneous human interferon β1 expressed in Escherichia coli was developed. Human interferon β1 ser17 gene was constructed, cloned and subcloned, and the recombinant protein expressed in E. coli cells. Solubilization of recombinant human interferon β1 ser17 (rhIFN-β1 ser17) was accomplished by employing a brief shift to high alkaline pH in the presence of non-ionic detergent. The recombinant protein was purifi ed by three chromatographic steps. N-terminal amino acid sequencing and mass spectrometry analysis provided experimental evidence for the identity of the recombinant protein. Reverse phase liquid chromatography demonstrated that the content of deamidates and sulphoxides was similar to a commercial standard. Size exclusion chromatography demonstrated the absence of high molecular mass aggregates and dimers. The protocol represents an effi cient and high-yield method to obtain bioactive homogeneous monomeric rhIFN-β1 ser17 protein. It may thus represent an important step towards scaling up for rhIFN-β1 ser17 large-scale production. © 2010 Villela AD, et al.
Keywords: Biopharmaceutical; Biosimilar; Escherichia coli; Non-ionic detergent; Recombinant human interferon β1 ser17; Recombinant protein production; interferon beta serine; bacterial cell; bioassay; biotechnological production; cell culture; controlled study; Daudi cell; DNA sequence; DNA synthesis; drug screening; gel permeation chromatography; genetic code; human; mass spectrometry; molecular cloning; molecular weight; nonhuman; nucleotide sequence; protein analysis; protein expression; protein purification; recombinant DNA technology; reversed phase liquid chromatography; solubilization